A study on organizational attributes and strategies for producing accurate digital twins in the architecture, engineering and construction (AEC) industry - Yuveelai Bunjaridh, Nop (2024)
The Architecture, Engineering and Construction (AEC) industry is experiencing a transformative shift towards digitalization, with the adoption of digital twin technology at its forefront. However, lacking technological advancement has caused the existence of a significant challenge concerning the production of digital twins. This challenge primarily stems from a need for more technological infrastructure and a low technological uptake within the industry. Moreover, the reluctance to change from current conventional construction working method has also hindered the production of digital twins. Digital twins, virtual replicas of physical assets and systems, have the potential to revolutionize how AEC organizations design, construct, and manage construction projects. The research aims to analyze the relationship between the organizational attributes and strategies to successfully produce accurate digital twins of construction projects within the AEC industry. To achieve the aim, the three objectives are: (1) to identify the organizational attributes and strategies in current AEC practices, (2) to determine key organizational attributes and strategies, and (3) to analyze the relationship of underlying constructs of organizational attributes and strategies to produce accurate digital twins of construction projects. The initial qualitative phase involved open-ended interviews with 20 Malaysia Building Information Modeling (BIM) professionals with digital twin knowledge, from BIM assistant managers to organization directors. The findings underlined three themes for organizational attributes (People, Process, and Technology) and strategies (Policy, Workflow, and Technology). The information gained from interviews, a comprehensive systematic literature review of 255 articles and a pilot study outlined the structure for the subsequent quantitative phase. This entailed distributing questionnaires to a broader array of construction professionals in Malaysia AEC industry. The outcome extracted 21 attributes and 30 strategies from the literature and the construction professionals’ interviews. Meticulous data analysis techniques were conducted. The mean score ranking technique yielded 11 key organizational attributes and 20 key strategies for producing accurate digital twins of construction projects. The Exploratory Factor Analysis (EFA) classified factors for organizational attributes into two groups (organizational digital twin capabilities and technological capabilities requirements) and organizational strategies into three groups (organizational competitiveness and investments, organizational workforce management and training, and organizational management capabilities). Six hypotheses were formulated, and three hypotheses were supported from the Partial-Least Structural Equation Modeling (PLSSEM) analysis. In conclusion, this research provides new evidence to AEC industry professionals for well-informed decision-making in producing accurate digital twins of construction projects, unlocking new levels of efficiency, sustainability, and innovation in the AEC industry.